Clinical presentation and outcome of Tuberculosis in Human Immunodeficiency Virus infected children on anti-retroviral therapy - Walters Lourens O; Schaaf H Simon; Rabie Helena; Cotton Mark F; Walters Elisabetta; Marais Ben J (BMC, 2008)
Abstract Background The tuberculosis (TB) and human immunodeficiency virus (HIV) epidemics are poorly controlled in sub-Saharan Africa, where highly active antiretroviral treatment (HAART) has become more freely available. Little is known about the clinical presentation and outcome of TB in HIV-infected children on HAART. Methods We performed a comprehensive file review of all children who commenced HAART at Tygerberg Children's Hospital from January 2003 through December 2005. Results Data from 290 children were analyzed; 137 TB episodes were recorded in 136 children; 116 episodes occurred before and 21 after HAART initiation; 10 episodes were probably related to immune reconstitution inflammatory syndrome (IRIS). The number of TB cases per 100 patient years were 53.3 during the 9 months prior to HAART initiation, and 6.4 during post HAART follow-up [odds ratio (OR) 16.6; 95% confidence interval (CI) 12.5-22.4]. A positive outcome was achieved in 97/137 (71%) episodes, 6 (4%) cases experienced no improvement, 16 (12%) died and the outcome could not be established in 18 (13%). Mortality was less in children on HAART (1/21; 4.8%) compared to those not on HAART (15/116; 12.9%). Conclusion We recorded an extremely high incidence of TB among HIV-infected children, especially prior to HAART initiation. Starting HAART at an earlier stage is likely to reduce morbidity and mortality related to TB, particularly in TB-endemic areas. Management frequently deviated from standard guidelines, but outcomes in general were good.